FILENG Filipino to English translation engine - Abella, Hannah Martha C. (2000)
In this fast-paced world wherein people continually come up with better ways to improve the way of life through technology, communication is a very important component. With the advent of new communication tools such as the Internet, satellites, fiber-optic cables and cellular phones, we are given more chances to communicate better with the rest of the world. These days, there is also an increasing trend of global ties and foreign trade. In this light, we need to address the problem of the language barrier in order for us to communicate more effectively with people from other nations. The Philippines has been coined as the 3rd largest English-speaking country in the world. In spite of this, not everyone can utter grammatically correct sentences - a factor which could lead to miscommunication. Thus, there is a need to create a tool that can aid Filipinos in communicating - a machine translator that can convert Filipino words and sentences to English. This study aims to create an application that translates Filipino sentences to English using various techniques in the field of Computational Lingustics. Specifically, a combination of Recursive Transition Networks (RTN) and Augmented Transition Networks (ATN) are employed using LISP. In addition, a lexical Database is designed to include parameters both for syntax and semantic checking. This project can pave the way for a fully accurate translation, both syntactically and semantically. It can eventually be incorporated into Internet chat, web page and email translation, or used as a learning tool or quick reference. With English as the dominant language in the international scene, Filipinos should equip themeselves with adequate communication skills in order to keep up with the rest of the world.